Effects of ileocolonic delivered vitamin B2, B3 and C (ColoVit) or the Groningen anti-inflammatory diet on disease course and microbiome of patients with Crohn's disease (VITA-GrAID study): a protocol for a randomised and partially blinded trial. Issue 3 (14th March 2023) - Otten, Antonius Timotheus; Peters, V; Barth, I; Stevens, C L; Bourgonje, A R; Frijlink, H W; Harmsen, H J M; Rehman, A; Campmans-Kuijpers, M J E; Dijkstra, G
Abstract : Background: Diet plays a pivotal role in the onset and progression of Crohn's disease (CD). Nutritional interventions revealed effects on intestinal inflammation and gut microbial composition. However, data from well-designed and controlled dietary trials are lacking. Therefore, evidence-based dietary recommendations are still unavailable to patients and physicians. Here, we aim to investigate the effects of an evidence-based anti-inflammatory diet, and an ileocolonic-targeted capsule containing vitamin B2, B3 and C (ColoVit) on patients with CD and their healthy household members. Methods and analysis: In this multicentre, randomised, placebo-controlled, partially blinded nutritional intervention trial, we aim to recruit 255 CD patients with Harvey-Bradshaw Index <8 and a faecal calprotectin (FCal) cut-off of ≥100 µg/g at baseline. Participants will be randomised into two experimental intervention groups and one placebo group. In the experimental groups, participants will either adhere to the Groningen anti-inflammatory diet (GrAID) or ingest an ileocolonic-delivered oral vitamin B2 /B3 /C capsule (ColoVit). The study consists of a 12-week controlled interventional phase, which proceeds to a 9-month observational follow-up phase in which patients allocated to the GrAID group will be requested to continue the intervention on their own accord. Household members of participating patients will be asked to participate in the trial as healthy subjects and are allocated to the same group as their peer. The primary study outcome for patients is the change in FCal level from baseline. The primary outcome for household members is the change in gut microbial composition, which is set as secondary outcome for patients. Ethics and dissemination: The protocol has been approved by the Institutional Review Board of the Stichting Beoordeling Ethiek Biomedisch Onderzoek in Assen, the Netherlands. Written informed consent will be obtained from all participants. Results will be disseminated through peer-reviewed journals and conference presentations. Trial registration number: NCT04913467 .